Haemophilus influenzae type b vaccine failure in children is associated with inadequate production of high-quality antibody. - Lee, Y; Kelly, D; Yu, L; Slack, M; Booy, R; Heath, P; Siegrist, C; Moxon, R; Pollard, A (2008)
BACKGROUND: Despite the excellent immunogenicity of Haemophilus influenzae type b (Hib) conjugate vaccines, breakthrough cases of Hib disease still affect a small proportion of vaccinated children in the United Kingdom. We performed a retrospective study to compare the avidity of antibody directed against the Hib polysaccharide capsule (PRP) in children who experienced Hib vaccine failure in the United Kingdom among 3 historical cohorts and with age-matched healthy control subjects. METHODS: Serum samples from vaccinated children with invasive Hib disease were collected beginning in 1992 as part of enhanced surveillance for Hib disease following vaccine introduction. A total of 251 children who experienced Hib vaccine failure were identified from 3 historical cohorts (1992-1995, 1996-1999, and 2000-2003). The anti-PRP antibody concentration and avidity from healthy age-matched control subjects was obtained for the 3 contemporary time points (1995, 1999, and 2002). Serum anti-PRP antibody concentration was measured in each of the samples using a standard Hib ELISA, and antibody avidity was determined using thiocyanate elution. RESULTS: Within the first 60 days after disease onset, there was no change in the anti-PRP antibody avidity, and there was no statistically significant difference in the geometric mean Hib antibody avidity over the 3 study periods. However, the children who experienced Hib vaccine failure had significantly lower Hib antibody avidity than did healthy control subjects, despite a marked antibody response following infection. CONCLUSIONS: Children who experience Hib disease despite vaccination appear to have a defect in immunological priming, leading to a qualitative difference in Hib-specific memory B cells. Low anti-PRP antibody avidity decreases the functional activity of anti-PRP antibody in the sera of these children experiencing vaccine failure, leading to disease susceptibility.